Role of Probiotic Strains in Ensuring Food Safety - Kisa, Jeniffer (Journal of Food Sciences, 2024)
Purpose: The general objective of this study was to examine the role of probiotic strains in ensuring food safety. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to the role of probiotic strains in ensuring food safety. Preliminary empirical review revealed that that probiotics offer promising avenues for enhancing microbial safety in food products. Through a comprehensive review of existing literature and empirical studies, researchers found that probiotics exhibited varied but significant antimicrobial activity against foodborne pathogens, thus reducing the risk of foodborne illnesses. The study emphasized the importance of strain-specific evaluation and standardized protocols for assessing probiotic efficacy. Furthermore, interdisciplinary collaborations were identified as crucial for translating scientific findings into practical applications for public health. Overall, the study highlighted the significant potential of probiotic strains in improving food safety outcomes, with further research needed to optimize formulations and address knowledge gaps. Unique Contribution to Theory, Practice and Policy: Ecological Theory of Gut Microbiota, Host-Microbiota Mutualism theory and Systems Biology Approach to Gut Microbiome may be used to anchor future studies on probiotic strains in ensuring food safety. The study emphasized advancing understanding of microbial ecology in the gastrointestinal tract, developing evidence-based guidelines for probiotic use, and aligning policies with scientific evidence. Recommendations included investing in research and education initiatives, fostering interdisciplinary collaborations, and promoting international cooperation. By integrating ecological principles, developing standardized protocols, and aligning policies with scientific evidence, stakeholders were able to harness the potential of probiotics to enhance food safety and public health, ultimately benefiting consumers worldwide.